The use of clustering in analysis of business lines in the insurance industry in conditions of crisis: The case of Lloyd's of London - Bożena Frączek; Zuzanna Roch (Contemporary Economics, 2024)
In an era of the overlapping effects of the Covid pandemic and the conflict in Ukraine, it is worth taking a closer look at the markets that focus on risk management, that is, the insurance market, in terms of its further organization and development. The aim of the paper is to examine how the crises related to the Covid-19 pandemic and the conflict in Ukraine have affected insurance business lines (using a case study of Lloyds). The study's use of clustering (Ward's method) for insurance business lines at Lloyd's, and its analysis within dynamically changing conditions, is expected to achieve preliminary classifications and insights for further more advanced research, resulting in more effective insurance activities. The impact of the discussed crises on cluster formation is significant. The study is divided into three main periods of analysis: the pre-Covid-19 period, the Covid-19 period and the Covid-19 recovery period (which occurred at the same time as the deepening of the conflict in Ukraine). Clustering highlighted the impact that the described crises have had on the performance of individual lines of business. In addition, it also turned out the division into clusters for insurance and reinsurance is not uniform. The exceptions are the years 2021 and 2022, in which clusters are formed identically for insurance and reinsurance. The results of the research highlight the necessity for further exploration of the study area in order to ensure the best possible further sustainable development of the insurance industry, and to better prepare it for any inconveniences or crises that may affect it.
Keywords: G22; 330; insurance; reinsurance; Covid-19; conflict in Ukraine; cluster analysis